L’urbanisme durable, utopie levantine ? - Stéphane Cartier (Territoire en Mouvement)
The financial speculation threats the Mediterranean towns. Beirut gathers degradation of dwelling, collapses and natural hazards, but also the investment in ostentatious architecture without inhabitants. There are natural, economic and social vulnerabilities. The land appropriation reinforces the inequities of dwelling and removes the population far away from the downtown. The development of luxurious towers without urban integration diffuses an urban design which destroys the natural resources and is dangerous for the population. The financial and political power of the investors orientates the application of the rules of urbanism. The application of anti-seismic codes is difficult in the instability of rules. The housing is not adapted to the natural constraints and also to the needs of the population. Beirut shows the gap between urban evolution and demographical growth on the Mediterranean coast. These situation calls for an integration of the ecologic and seismic constraints in the planning of the cities according to the needs of the inhabitants.